2013
DOI: 10.3233/nre-131003
|View full text |Cite
|
Sign up to set email alerts
|

Effects of non-paretic arm exercises using a tubing band on abdominal muscle activity in stroke patients

Abstract: BACKGROUND: Abdominal strengthening exercises are important for stroke patients; however, there is a lack of research on therapeutic exercises for increasing abdominal muscle activity in stroke patients. OBJECTIVE: We investigated the effects of non-paretic arm exercises using a tubing band on abdominal muscle activity in stroke patients. METHODS: In total, 18 hemiplegic subjects (13 males, 5 females) were recruited. All subjects performed non-paretic arm exercises involving three different shoulder movements … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 16 publications
1
7
0
Order By: Relevance
“…In addition, when the posture with hip abduction was maintained in the stance position, the activity of the anterior muscles of the trunk was greater on an unstable surface than in the stable basal plane [12]. As shown in the above study, the addition of limb movements to the trunk muscle stabilization exercises further increased abdominal activation [13], and in particular, the movement of one limb further increased the activity of the abdominal muscles associated with trunk stability [14]. Although there are several studies that show that plank exercises are effective, there are few studies that have investigated the activation of trunk muscles during plank exercises according to postural changes [9], and studies with limb movements during modified plank exercise are also lacking.…”
Section: Original Articlementioning
confidence: 58%
See 1 more Smart Citation
“…In addition, when the posture with hip abduction was maintained in the stance position, the activity of the anterior muscles of the trunk was greater on an unstable surface than in the stable basal plane [12]. As shown in the above study, the addition of limb movements to the trunk muscle stabilization exercises further increased abdominal activation [13], and in particular, the movement of one limb further increased the activity of the abdominal muscles associated with trunk stability [14]. Although there are several studies that show that plank exercises are effective, there are few studies that have investigated the activation of trunk muscles during plank exercises according to postural changes [9], and studies with limb movements during modified plank exercise are also lacking.…”
Section: Original Articlementioning
confidence: 58%
“…Plank exercises are popular and beneficial in rehabilitation programs [17], and the abdominal muscles of the trunk are more active when compared to the trunk extensors [5]. The movement of the limbs, such as hip joint adduction and abduction, contributes to the transfer of force to the trunk muscles through the ASIS [7], and activation of the abdominal muscles with additional limb movements has been reported to occur with larger amplitudes when the predicted instability is applied to the trunk and when the activation patterns of the abdominal muscle is associated with the direction of limb movement [13,14,18].…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that loaded shoulder movements increase trunk muscle activity 12 , 13 ) . Researchers have suggested that shoulder movements facilitate trunk muscle activity to counteract the postural demands or reactive force caused by shoulder movement 12 , 13 , 14 ) . From this point of view, squat exercises with loaded shoulder movements may lead to greater electromyographic activity in the gluteal muscles, as well as the trunk muscles, while maintaining appropriate alignment of the lower extremity.…”
Section: Introductionmentioning
confidence: 99%
“…Aruin and Latash7 ) reported that the activity pattern of the trunk muscles was related to the direction of limb movement. Also, Lee et al8 ) in a study using Thera-band in hemiplegia patients with stroke, reported that the external oblique, which is a trunk rotator, on the paretic side showed significantly higher activity in non-paretic arm extension and abduction than did that on the non-paretic side. These studies suggest methods that use the non-paretic side to increases trunk muscle strength on the paretic side in therapeutic exercises with hemiplegic patients.…”
Section: Introductionmentioning
confidence: 99%